Association between Dietary Nutrient Intake and Depressive Symptoms among Japanese Postpartum Women: An Observational Cross-sectional Study - Rina Nakajima; Masayo Matsuzaki; Mie Shiraishi; Emi Sasagawa-Tahara; Megumi Haruna (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2023)
Background: Low dietary nutrient intake may be associated with depressive symptoms. However, few such studies have been conducted among postpartum women and results have been controversial. Purpose: To investigate the association between dietary nutrient intake and depressive symptoms among Japanese one-month postpartum women. Methods: This cross-sectional study was conducted at a university hospital in Tokyo from June 2015 to September 2016. We recruited healthy women with healthy babies at their postpartum check-up. Dietary nutrient intake was assessed using a validated, brief-type, self-administered diet history questionnaire. Depressive symptoms were defined as a score of ? 9 on the Edinburgh Postnatal Depression Scale. Multiple logistic regression analysis was performed to identify if dietary nutrient intake was associated with depressive symptoms. Variables with P-values < 0.10 in the bivariate analysis and factors identified as important, based on the literature review, were included. P < 0.05 was considered significant. Results: Data from 246 participants were analyzed. Depressive symptom prevalence was 19.5%. Participants with an educational level above university level comprised 69.1%, and 68.3% of participants had a household income of ? 7 million Japanese yen. In the multivariate analysis, dietary nutrient intake was not significantly associated with depressive symptoms. However, higher educational level and need for emotional support as assessed by midwives or nurses were significantly associated with an increased risk of depressive symptoms. Conclusion: Dietary nutrient intake was not significantly associated with depressive symptoms in this high socioeconomic status population. Further research is needed to identify the relationship between dietary intake and depressive symptoms among more socioeconomically diverse postpartum women. Additionally, it may be important for postpartum depression support systems to pay attention to highly-educated women and to undertake continued follow-up for women who are assessed by midwives or nurses as needing emotional support either during pregnancy or while in the hospital.